2012
DOI: 10.1007/s11325-012-0703-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation and paraoxonase activity in nocturnal cyclic and sustained intermittent hypoxia

Abstract: The results of this study revealed that both OSA and non-apneic, nocturnal desaturated COPD patients showed increased levels of lipid peroxidation and decreased PON activity despite the differences in nocturnal hypoxia pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 47 publications
1
19
0
1
Order By: Relevance
“…. In accordance with the previous studies and based on our data, we conclude that the systemic high oxidative stress in OSA increases protein oxidation to some extent as indicated by significantly higher AOPP levels .…”
Section: Discussionsupporting
confidence: 93%
“…. In accordance with the previous studies and based on our data, we conclude that the systemic high oxidative stress in OSA increases protein oxidation to some extent as indicated by significantly higher AOPP levels .…”
Section: Discussionsupporting
confidence: 93%
“…In addition to our research, Kuzu Okur and colleagues noted significantly lower levels of PON1 in COPD patients compared with controls. 103 Torres-Ramos and coworkers related COPD to CVD by pointing out significantly decreased PON1 activity in more severe forms of COPD and its inverse association with the concentration of lipid hydroperoxides. 104 Moreover, it has been found that genotype distribution of PON1 Q192R gene polymorphism differed significantly between COPD patients and controls with frequency of the QQ phenotype being higher and while the RR phenotype was absent in controls.…”
Section: Pon1 and Renal Diseasementioning
confidence: 99%
“…Several studies reported perturbation in oxidative and antioxidant balance in patients with OSA [14,15]. There are several reports on PON activities in OSA patients; however, the results are inconsistent [16,17]. Therefore, the present study aimed to reassess the published studies on PON activity in OSA patients compared with controls.…”
Section: Introductionmentioning
confidence: 91%
“…A total of 5 studies including 131 OSA patients and 93 controls were included in the meta-analysis [16,[19][20][21][22]. All studies had reported PON activity, while two studies had reported ARE activity, and no study had reported LAC activity.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%